2018
DOI: 10.1080/15384047.2018.1504725
|View full text |Cite
|
Sign up to set email alerts
|

Adeno-associated virus 2 mediated gene transfer of vascular endothelial growth factor Trap: a new treatment option for glioma

Abstract: Background: Adeno-associated virus 2 mediated gene transfer of vascular endothelial growth factor Trap (AAV2-VEGF-Trap) has been reported to inhibit the growth of primary tumor as well as distant metastasis in 4T1 metastatic breast cancer models. The aim of this study was to investigate the inhibiting efficacy of AAV2-VEGF-Trap for glioma. Methods: The intracranial transplanted model of glioma in rats was established. They were treated with AAV2-VEGF-Trap, bevacizumab (BEV), temozolomide (TMZ), TMZ combined wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Moreover, the same approach was used in a rat GBM model in combination with temozolomide, a chemotherapeutic drug widely used for GBM treatment. Again, a single tail vein injection of AAV2-VEGF-Trap [ 162 ] resulted in long-term expression and synergistic growth inhibitory effects were seen in combination with chemotherapy. Finally, anti-angiogenic effects were monitored by Magnetic Resonance Imaging (MRI) [ 162 ].…”
Section: Use Of Aav Vectors For Cancer Gene Therapy In Preclinicalmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the same approach was used in a rat GBM model in combination with temozolomide, a chemotherapeutic drug widely used for GBM treatment. Again, a single tail vein injection of AAV2-VEGF-Trap [ 162 ] resulted in long-term expression and synergistic growth inhibitory effects were seen in combination with chemotherapy. Finally, anti-angiogenic effects were monitored by Magnetic Resonance Imaging (MRI) [ 162 ].…”
Section: Use Of Aav Vectors For Cancer Gene Therapy In Preclinicalmentioning
confidence: 99%
“…Again, a single tail vein injection of AAV2-VEGF-Trap [ 162 ] resulted in long-term expression and synergistic growth inhibitory effects were seen in combination with chemotherapy. Finally, anti-angiogenic effects were monitored by Magnetic Resonance Imaging (MRI) [ 162 ]. A similar approach was performed in a triple negative breast cancer model (MDA-MB-231).…”
Section: Use Of Aav Vectors For Cancer Gene Therapy In Preclinicalmentioning
confidence: 99%
“…Adeno-associated virus (AAV) gene therapy vectors are safe [ 31 ] and effective in vivo gene delivery vehicles that promote long-term transgene expression [ 32 , 33 ], with applications to cancer treatment [ 34 , 35 , 36 , 37 , 38 , 39 , 40 ]. AAV has been used to express a wide array of anti-cancer agents including endostatin [ 41 , 42 ], angiostatin [ 43 , 44 ], pigment epithelium-derived factor (PEDF) [ 45 ], and VEGF-Trap [ 46 , 47 ], to name a few. Results from these and other studies indicate that systemic expression of antiangiogenic agents from AAV represents a potentially effective cancer treatment [ 48 ], either alone or in combination with other therapies such as chemotherapeutic drugs [ 18 , 49 ].…”
Section: Introductionmentioning
confidence: 99%
“…9 Animal studies have demonstrated that the growth of breast cancer and glioma can be inhibited by a single injection of AAV2-VEGF-Trap. 9,10 In this report, we aimed to evaluate the antitumor efficacy of AAV2-VEGF-Trap alone or combination with paclitaxel in a TNBC animal model.…”
Section: Introductionmentioning
confidence: 99%
“…Gene therapy using adeno‐associated virus 2 (AAV2) to deliver VEGF‐Trap achieved long‐term expression of VEGF‐Trap in vitro and in vivo . Animal studies have demonstrated that the growth of breast cancer and glioma can be inhibited by a single injection of AAV2‐VEGF‐Trap . In this report, we aimed to evaluate the antitumor efficacy of AAV2‐VEGF‐Trap alone or combination with paclitaxel in a TNBC animal model.…”
Section: Introductionmentioning
confidence: 99%